BER and outage probability for cooperative relay networks - Ng, Chee Hou (2017)
In every cooperative relay system, there is a protocol to define the cooperating strategy of the system. The protocols studied in this report consist of amplify-and-forward (AF), fixed decode-and-forward (FDF), selective decode-and-forward (SDF), and hybrid decode-amplify-forward (HDAF). A simple three-nodes model of cooperative relay system is used to simulate each protocol’s performance, with regards to its bit error rate (BER) and outage probability. This report analyses and highlights on the gain in performance achieved when employing cooperative communication over a direct point-to-point wireless transmission system. Apart from FDF, all other protocols have shown to achieve a significant gain of over 10 dB and 9 dB at a BER and an outage probability of 10-4, respectively. FDF instead shows no achievable gain in BER and has a poorer result in outage probability. With the increment of phase-shift keying (PSK) modulation size, AF shows the best BER performance when modulating with the BPSK scheme, while HDAF excels in both QPSK and 8PSK schemes. Using the outage probability metric, SDF and HDAF give the best comparable performance.